To Assess The Knowledge And Perceptions Regarding Novel Coronavirus (Covid-19) During The First Surge Among Healthcare Workers Of Banke District, Nepal (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Human Coronaviruses (HCoVs), a large family of single-stranded RNA viruses in humans causes mainly respiratory tract infections. The current outbreak of coronavirus disease 2019 has emerged as pandemic causing severe public health issue of international concern. This study aims to assess the knowledge and perception regarding novel coronavirus (COVID-19) during first wave of pandemic among healthcare workers working at various Health care institutions.Method: This web-based cross-sectional study was conducted among 174 health care workers of Banke district, Nepal between May-July 2020 during first wave of COVID-19 pandemic using an online self-administered questionnaire. A 35-item self-administered survey instrument was developed using WHO course materials on emerging respiratory viruses, including COVID-19, and covered the domains of HCWs characteristics, knowledge, and perceptions of HCWs related to COVID-19. Descriptive statistics were reported as proportion and frequencies. Bivariate analysis was performed using chi-square test to assess the association of level of knowledge, and perception about COVID-19 with participants’ characteristics. A p-value of less than 0.05 was considered statistically significant. All the statistical analysis was performed using IBM SPSS software, version 23.Findings: Most of the participants (94.8%) had known about the virus from news (70.1%) and social media (68.4%). Among them only 36.2% participants had the opportunities to attend lectures, discussions, and training about the virus COVID-19. Overall, 55.7%, and 52.9% of the HCWs had adequate knowledge, and positive perception about COVID-19, respectively. Bivariate analysis showed no significant association of knowledge regarding COVID-19 among health care worker with participants characteristics whereas, the variables such as gender, occupation, working department showed significant association of perception regarding COVID-19 among health care worker.Conclusion: This study revealed lower level of knowledge and positive perception regarding COVID-19 and infection control measures among HCWs. There is a need of adequate training to enhance the knowledge and perception about covid-19 and safety measures to the HCWs.